Introduction to econometrics : principles and applications - Kelejian, Harry H.; Oates, Wallace, E. (New York : Harper & Row, 1981)
The basic purpose in this edition is unchanged from that in the first edition: it seeks to present a wide range of econometric techniques based on only elementary mathematical and statistical skills. For a description of the method, it refers the reader to the accompanying Preface to the First Edition
Includes index.
oif 07/04/15
Loans
Keywords: Econometrics